Stratigraphic occurrences of sub-polar planktic foraminifera in Pleistocene sediments on the Lomonosov Ridge, Arctic Ocean - O'Regan, Matthew; Kaboth-Bahr, Stefanie (Frontiers in Earth Science, 2019)
Turborotalita quinqueloba is a planktonic foraminifera commonly found in the sub-polar North Atlantic, and along the pathway of Atlantic waters in the Nordic seas. Although scarce in Holocene sediments from the central Arctic Ocean, abundances of this sub-polar species increase in sediments from the Last Interglacial Period (Marine isotope stage (MIS) 5, 71-120 ka) in cores off the northern coast of Greenland and the southern Mendeleev Ridge. Turborotalita species also occur in earlier Pleistocene interglacials in these regions, with a unique and widespread occurrence of the Turborotalita egelida morphotype, proposed as a biostratigraphic marker for MIS 11 (474-374 ka). Here we present results from 6 new sediment cores, extending from the central to western Lomonosov Ridge, that map a consistent Pleistocene stratigraphy over 575 km. In one of these records (LOMROG12-07PC) we find three distinct stratigraphic horizons containing Turborotalita. Based on the cyclostratigraphic age model for the Pleistocene section of the Integrated Ocean Drilling Program’s Expedition 302 (The Arctic Coring Expedition - ACEX), these occurrences are in MIS 5.1, 5.5 and 9. Specimens from these intervals closely resemble T. quinqueloba, but are small (63-125 μm) and not encrusted, similar to contemporaneous sediments from the Lomonosov Ridge bordering Greenland, but distinct from typical encrusted forms found in the Norwegian Greenland Seas. These results extend the range for T. quinqueloba in MIS 5 sediments of the Arctic Ocean, and provide compelling evidence for recurrent invasions during Pleistocene interglacials. Further work is needed to 1) determine the taxonomic relationships between T. quinqueloba and T. egelida, 2) acquire additional age control to anchor the earlier appearance of Turborotalita and 3) establish whether the sporadic occurrence reflects anomalous oceanographic conditions during some Pleistocene interglacials, or is a consequence of post-depositional dissolution.
Gesehen am 26.03.2020